International Student’s Guide to American Colleges - Dennis, Marguerite J. (Journal of International Students, 2015)
In the opening pages of The International Student’s Guide to American Colleges, the author lays out in a clear and organized way the purpose of the book, which is to assist international students in figuring out the type of American college or university that is best for them and to provide the tools needed to build their college lists.